Pengaruh Media Visual Tentang Penatalaksanaan Hipertensi Terhadap Sikap dan Perilaku Penderita Hipertensi - Susanto, Bela Novita Amaris; Rahayuningsih, Tutik; Setyaningsih, Ratna (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Health education or promotion is part of hypertension management to control hypertension. Visual media is often used in health promotion activities, because the material displayed is easy to understand and interesting. So far, society has controlled or reduced hypertension only pharmacologically, and is not familiar with complementary therapies for managing hypertension. Good public knowledge will influence positive attitudes and behavior. The aim of this research is to determine the effect of using visual media regarding hypertension management on the attitudes and behavior of hypertension sufferers. Research with one group pretest posttest design with a sample size of 30 respondents from Gesono Village, Wonosegoro District, Boyolali Regency. Data analysis used the independent t test. The results of data analysis show that there is an influence of visual media regarding hypertension management on attitudes (p<0.001) and behavior (p=0.001) in hypertension sufferers. There is a significant influence of visual media on the management of hypertension with the behavioral attitudes of hypertension sufferers in Gesono Village, Wonosegoro District, Boyolali Regency.